2009
DOI: 10.1007/s00134-009-1687-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vasopressin on acute kidney injury in septic shock

Abstract: Kidney injury was present in 464 patients (59.6%) at study entry. In patients in the RIFLE "Risk" category (n=106) vasopressin as compared with norepinephrine was associated with a trend to a lower rate of progression to renal "Failure" or "Loss" categories (20.8% v 39.6% respectively, p=0.03), and a lower rate of use of renal replacement therapy (17.0% v 37.7%, p=0.02). Mortality rates in the "Risk" category patients treated with vasopressin compared to norepinephrine were 30.8% v 54.7%, p=0.01, but this did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(134 citation statements)
references
References 32 publications
3
126
1
4
Order By: Relevance
“…Being encapsulated, the kidneys are also extremely vulnerable to compression by evolving edema. The VASST study reported no significant differences in fluid volume, fluid balance, or diuretic use during the first 4 days between vasopressinand noradrenaline-treated patients at risk for SAKI (3). However, no data on baseline or serial preload measurement were provided.…”
Section: Gordon Et Al Recently Reported the Results Of The Multicentmentioning
confidence: 99%
“…Being encapsulated, the kidneys are also extremely vulnerable to compression by evolving edema. The VASST study reported no significant differences in fluid volume, fluid balance, or diuretic use during the first 4 days between vasopressinand noradrenaline-treated patients at risk for SAKI (3). However, no data on baseline or serial preload measurement were provided.…”
Section: Gordon Et Al Recently Reported the Results Of The Multicentmentioning
confidence: 99%
“…Prior studies have shown a positive effect of AVP use on kidney function (3,7,17) and a positive interaction between AVP and corticosteroid use (4,18), both findings which were not corroborated in VANISH. There are many differences in the prior trials and VANISH, including how AVP was utilized and the timing of corticosteroid initiation.…”
mentioning
confidence: 75%
“…A post hoc analysis of the VASST trial found that a subgroup of patients had a lower progression rate to renal failure [86]. The physiological rationale is that vasopressin constricts the efferent as opposed to NA predominantly constricting the afferent renal vessel [86].…”
Section: The Effect Of Vasopressors On Splanchnic Perfusion In the Sementioning
confidence: 99%